Diagnostic and prognostic value of HSPD1 in oesophageal cancer. (7th July 2022) - Chen, Xin; Luo, Can; Bai, Yuting; Zhou, Xi; Xu, Lei; Guo, Xiaolan; Wu, Qing; Zhong, Xiaowu
HSPD1 is a potential biomarker in many cancers. However, its role in oesophageal cancer (ESCA) is poorly understood. Among patients with ESCA, a high HSPD1 expression is linked to a poor outcome. As suggested by Cox analysis results combined with ROC (receiver operating characteristic) graph, HSPD1 is an independent outcome predictor for the ESCA population and had a diagnostic value. Moreover, HSPD1 is linked to immunofiltration, genetic alteration and methylation in ESCA, which is also involved in biological processes, such as chaperonin-containing T-complex, PI3K/Akt signalling pathway, and thyroid hormone signalling pathway. According to a final analysis of drug susceptibility, low HSPD1 expression is correlated with resistance to 23 drugs. This phenomenon provided new insights for the probable predictor role of HSPD1 in the ESCA diagnosis and prognosis.